Research on Surface Failure Law of Working Faces in Large Mining Height and Shallow Buried Coal Seam - Zhenhua Li; Yingkun Pang; Yongsheng Bao; Zhanyuan Ma (Advances in Civil Engineering)
In the process of high-intensity and large-space mining in Shendong mining area, various surface cracks are generated on the surface, resulting in serious damage to the surface buildings and the local ecological environment. To study the influence of overlying rock movement on surface failure of near-field single key strata of near-shallow buried and large mining height working face, the relationship between overburden movement, strata pressure appearance, and surface failure at working face 52307 in Daliuta mining area was analyzed by field measurement and numerical simulation. The results show the following: (1) there is only one thick and hard key stratum in the overburden of large mining height and near-shallow buried working face. Under the condition of presplitting roof blasting, the first weighting step is still as high as 95 m, and the periodic breaking step of roof is 20–30 m. During the weighting, the working resistance of support is still close to the rated resistance. (2) The single key stratum plays an obvious role in controlling overburden movement. After the first weighting of the working face, a stepped subsidence crack appears on the surface within a short time, and the crack lags behind the working face for about 5 m. (3) During each periodic weighting process, the breaking and subsidence of key blocks are accompanied by surface cracks.